2000
DOI: 10.1128/jvi.74.17.7980-7988.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of a Very Virulent Marek's Disease Virus

Abstract: Here we present the first complete genomic sequence, with analysis, of a very virulent strain of Marek's disease virus serotype 1 (MDV1), Md5. The genome is 177,874 bp and is predicted to encode 103 proteins. MDV1 is colinear with the prototypic alphaherpesvirus herpes simplex virus type 1 (HSV-1) within the unique long (UL) region, and it is most similar at the amino acid level to MDV2, herpesvirus of turkeys (HVT), and nonavian herpesviruses equine herpesviruses 1 and 4. MDV1 encodes 55 HSV-1 UL homologues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
224
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(234 citation statements)
references
References 100 publications
6
224
0
4
Order By: Relevance
“…This extended deletion resulted in the loss of EcoRI site corresponding to position 7,100, and therefore, the 1,370-bp EcoRI fragment from the TR L migrated as a 5,063-bp fragment. Sequence analysis of this extended deletion indicated that no other large contiguous ORFs were deleted (14). However, because splicing and sense͞ antisense expression in this region is highly complex, it may affect gene expression.…”
Section: Construction Of Meq Deletion Mutant Rmd5⌬meqmentioning
confidence: 99%
“…This extended deletion resulted in the loss of EcoRI site corresponding to position 7,100, and therefore, the 1,370-bp EcoRI fragment from the TR L migrated as a 5,063-bp fragment. Sequence analysis of this extended deletion indicated that no other large contiguous ORFs were deleted (14). However, because splicing and sense͞ antisense expression in this region is highly complex, it may affect gene expression.…”
Section: Construction Of Meq Deletion Mutant Rmd5⌬meqmentioning
confidence: 99%
“…Horizontal spread, thus far, is the only property lacking in rRB-1B to make it a full model to study MDV biology. Despite this shortcoming, pRB-1B and its derivatives are great tools to determine the molecular determinants involved in MDV horizontal dissemination in birds by individual, consequential or concomitant repair of genes that are found to be different from authentic, wild-type MDV [17,32].…”
Section: Introductionmentioning
confidence: 99%
“…The MDV genome is approximately 185 kbp in size and encodes at least 103 proteins [32]. Several MDV genomes have been cloned as bacterial artificial chromosomes, including an avirulent strain (584Ap80C) (yielding the bacmid BAC20) and the highly virulent strain RB-1B (yielding the bacmid pRB-1B) [21,26].…”
Section: Introductionmentioning
confidence: 99%
“…Wirus MDV z powodu swej limfotropowej natury początkowo klasyfikowany był jako Gammaherpesvirinae, jednak w 2002 r., po uzyskaniu pełnej sekwencji genomu nastąpiła jego reklasyfikacja do nowego rodzaju Mardivirus (41), w obrębie którego wyodrębniono jeszcze 4 inne gatunki, tj. : Gallid herpesvirus 3 (GaHV-3), Meleagrid herpesvirus 1 (MeHV-1) -znany także pod nazwą herpesvirus indyków (HVT), Anatid herpesvirus 1 i Columbid herpesvirus 1.…”
Section: Artykuł Przeglądowy Reviewunclassified